Comparison of radar derived rain attenuation with the RazakSAT’s X-Band link signal measurement - Badron, Khairayu; Ismail, Ahmad Fadzil; Jusoh, Ahmad Zamani; Ismail , Maszlan; Hashim, Wahidah (International Association of Computer Science and Information Technology Press, 2013)
Abstract—The preliminary analysis involving comparison between radar derived attenuation using an S-band meteorological radar and measured signal of RazakSAT’s X-band satellite link is presented. The radar data employed was attained from the Malaysian Meteorological Department’s (MMD) terminal Doppler weather radar installed strategically in the vicinity of Kuala Lumpur International Airport (KLIA). The X-band (8 GHz) satellite-Earth signals of Malaysian RazatSat’s collected at the National Space Agency (NSA) space center have been analyzed and studied. The vertical polarization S-band radar reflectivity information was used to calculate the likely rain attenuation along the RazakSAT satellite propagation paths. This was carried out by first converting the radar reflectivity values into rainfall rate using the established Z-R relations of Marshall-Palmer equation and, afterwards, by evaluating the slant path attenuation through the assimilation of the specific rain attenuation derived at the rainfall rate.